2018
DOI: 10.17509/bs_jpbsp.v17i2.9658
|View full text |Cite
|
Sign up to set email alerts
|

Metode Total Physical Response (Tpr) Pada Pengajaran Bahasa Inggris Siswa Taman Kanak-Kanak

Abstract: AbstrakMetode TPR adalah salah satu metode untuk pengajaran bahasa pada anak usia dini karena penerapannya berhubungan antara koordinasi perintah, ucapan dan gerak sehingga seorang anak lebih mudah untuk menguasai suatu bahasa dalam pembelajarannya. Tujuan penelitian ini adalah untuk menganalisis bagaimana guru TK Aisyiyah 5 Tanggulangin mengajarkan bahasa Inggris dengan metode TPR pada siswanya. Metode penelitian ini menggunakan desain kualitatif deskriptif. Non partisipan observasi dan wawancara dilakukan se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
7
0
7
Order By: Relevance
“…Asher concluded that the interaction between parents and children is often in the form of speech and responded to by physical activity by children. Asher [14] suggests that direct pronunciation to children contains a command, so that the child will respond physically (body language) before they start to produce a verbal response. So that it can be said that "Total Physical Response (TPR) or Total Physical Response is a method of learning English that is suitable for early childhood where learning is more focused on activities that are directly related to physical activity and movement.…”
Section: B Total Physical Response (Tpr) Learning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asher concluded that the interaction between parents and children is often in the form of speech and responded to by physical activity by children. Asher [14] suggests that direct pronunciation to children contains a command, so that the child will respond physically (body language) before they start to produce a verbal response. So that it can be said that "Total Physical Response (TPR) or Total Physical Response is a method of learning English that is suitable for early childhood where learning is more focused on activities that are directly related to physical activity and movement.…”
Section: B Total Physical Response (Tpr) Learning Methodsmentioning
confidence: 99%
“…The application of the TPR model in English for early childhood is suitable to be applied to kindergarten children. Larsen & Freeman [14] also states that in the first stage of the TPR method, the teacher acts as a model that demonstrates the action. The teacher can give instructions to some of his students and then give examples or practice his words in front of the students so that students can understand instructions or commands given and can follow the words and movements of the teacher's instructions.…”
Section: B Total Physical Response (Tpr) Learning Methodsmentioning
confidence: 99%
“…Hal tersebut dilakukan melalui pemberian rangsangan pendidikan untuk membantu pertumbuhan dan perkembangan jasmani dan rohani agar anak memiliki kesiapan dalam memasuki pendidikan lebih lanjut dan juga mengacu pada Permendikbud, Pasal 7 bahwa mengingat pembelajaran bahasa Inggris diberikan kepada anak sejak dini, maka dalam pembelajarannya perlu disesuaikan dengan tingkat perkembangan anak. Menurut Standar Tingkat Pencapaian Perkembangan Anak Pasal sebagaimana dimaksud ayat (1) merupakan integrasi dari perkembangan aspek nilai agama dan moral, fisikmotorik, kognitif, bahasa, dan sosial emosional, serta seni [3].…”
Section: Pendahuluanunclassified
“…Asher, 1968). Astutik & Aulina (2018) dalam penelitiannya mengenai pengajaran Bahasa Inggris untuk siswa Taman Kanak-kanak menemukan bahwa guru-guru di TK Aisyiyah 5 Tanggulangin, Indonesia menggunakan metode TPR dalam mengajarkan Bahasa Inggris baik di dalam maupun di luar kelas dan tidak terbatasi oleh waktu pelajaran Bahasa Inggris. Selain mengikuti gerakangerakan yang dicontohkan guru, anak-anak yang menjadi partisipan dalam penelitian itu juga meresponnya dalam bentuk verbal.…”
Section: Pemahaman Kosakata Bahasa Inggris Untuk Anak Anak Melalui Lagu Ima Widyastuti Dan Victa Sari Dwi Kurniatiunclassified